Associations of microRNA single nucleotide polymorphisms and disease risk and pathophysiology. Issue 3 (19th March 2017) - Liu, X.; Han, Z.; Yang, C.
Abstract : Single nucleotide polymorphisms (SNPs) are genetic variations that contribute to human phenotypes associated with various diseases. SNPs are involved in the regulation of a broad range of physiological and pathological processes, such as cellular senescence, apoptosis, inflammation, and immune response, by upregulating the expression of classical inflammation markers. Recent studies have suggested that SNPs located in gene‐encoding microRNAs (miRNAs) affect various aspects of diseases by regulating the expression or activity of miRNAs. In the last few years, miRNA polymorphisms that increase and/or reduce the risk of developing many diseases, such as cancers, autoimmune diseases, and cardiovascular diseases, have attracted increasing attention not only because of their involvement in the pathophysiology of diseases but also because they can be used as prognostic biomarkers for a variety of diseases. In this review, we summarize the relationships between miRNA SNPs and the pathophysiology and risk of diseases.